Facilitators and challenges in recruiting pregnant women to an infant obesity prevention programme delivered via telephone calls or text messages - Ekambareshwar, Mahalakshmi; Mihrshahi, Seema; Wen, Li Ming; Taki, Sarah; Bennett, Greer; Baur, Louise A.; Rissel, Chris (Current controlled trials in cardiovascular medicine, 2018)
Background Recruitment of pregnant women into trials is a challenge exacerbated by a number of factors, including strict eligibility criteria. There has been little in-depth examination of the recruitment process to trials involving pregnant women. This paper presents the findings of a study conducted to identify facilitators and challenges in recruiting pregnant women to the Communicating Healthy Beginnings Advice by Telephone (CHAT) randomised controlled trial, which aims to reduce the prevalence of infant and childhood obesity. Methods Data were collected from (1) administration of a short questionnaire to women at the time of recruitment exploring women’s reasons for consent and non-consent; (2) interviews with recruiters to capture recruiters’ experiences of the recruitment process; and (3) analysis of field notes taken by recruiters on the number of women approached/recruited and reasons as to why they did not consent to participate. Data obtained were triangulated to gain insights into the process of recruiting pregnant women. Results A total of 1155 pregnant women (mean gestational age 31.5 weeks) were enrolled over 5 months. The main reasons for women consenting to participate in the study were convenience in programme delivery mode via telephone calls or text messages, altruism and because the programme was free of charge. The main reasons for women not consenting were lack of interest, language challenges/difficulty speaking English and some felt they did not need information and support due to prior experience as a mother. Facilitators included organisational support, rapport with recruiters and some women with no other children who needed advice. Despite the challenges, the mode of delivery of intervention via telephone calls or text messages, the minimal effort required of women to participate, organisational support from the lead site and recruiters’ knowledge of and commitment towards the trial contributed towards successful recruitment. Conclusion Despite some challenges in recruiting pregnant women to an infant obesity prevention programme, some of the facilitators in recruitment included mode of delivery of the intervention programme via telephone calls or text messages, the minimal effort required for women to participate, organisational support from the lead site, and recruiters’ knowledge of and commitment towards the trial. Trial registration The CHAT RCT is registered with the Australian Clinical Trial Registry ( ACTRN12616001470482p ); Ethics Review Committee of Sydney Local Health District (Protocol No. X16–0360 & LNR/16/RPAH/495).